2023
DOI: 10.1021/acs.cgd.3c00185
|View full text |Cite
|
Sign up to set email alerts
|

Stable CdII-Based Metal–Organic Framework as a Multiresponsive Luminescent Sensor for Acetylacetone, Salicylaldehyde, and Benzaldehyde with High Sensitivity and Selectivity

Abstract: A class of potential luminescent sensing materials has been gradually developed in the form of luminescent metal–organic frameworks (LMOFs). A new LMOF with the formula {[Cd(BBZB)(bptc)0.5]·2H2O} n (JXUST-33, BBZB = 4,7-bis(1H-benzimidazole-1-yl)-2,1,3-benzothiadiazole, H4bptc = biphenyl-3,3′,5,5′-tetracarboxylic acid) has been successfully constructed, which exhibits the stability of structure and effectiveness of luminescence. Single-crystal X-ray diffraction studies have shown that two adjacent CdII ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, there is no overlap for the emission spectra of two CPs with the absorption spectra of UA, and there are partial overlaps for the emission spectra of two CPs with the absorption spectra of MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– . This suggests that the competitive absorption is an important reason for the luminescence quenching effects toward UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– . , Finally, there is almost no significant change in the luminescence lifetimes of 1 and 2 before and after adding UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– (Figure S22), indicating that the luminescence quenching effects toward UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– are static quenching processes …”
Section: Results and Discussionmentioning
confidence: 95%
“…However, there is no overlap for the emission spectra of two CPs with the absorption spectra of UA, and there are partial overlaps for the emission spectra of two CPs with the absorption spectra of MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– . This suggests that the competitive absorption is an important reason for the luminescence quenching effects toward UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– . , Finally, there is almost no significant change in the luminescence lifetimes of 1 and 2 before and after adding UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– (Figure S22), indicating that the luminescence quenching effects toward UA, MnO 4 – , CrO 4 2– , and Cr 2 O 7 2– are static quenching processes …”
Section: Results and Discussionmentioning
confidence: 95%
“…This change in solution fluorescence was also achieved through color changes observed with the naked eye under ultraviolet light (inset of Figure 5 b). The relationship between the emission intensities of MOF-1 and the DPA concentration is illustrated in Figure 5 c. At low DPA concentrations, the fluorescence enhancement curve can be quantitatively calculated with the Stern–Volmer equation (S-V): I 0 /I = 1+ K sv [M] [ 44 ] ( I 0 /I represents the ratio of emission intensity before and after DPA addition to MOF-1, [M] represents the concentration of DPA, and K sv represents the fluorescence enhancement constant). As we expected, the detection of DPA had a satisfactory linear relationship (R 2 > 0.98), and the enhancement constant ( K sv ) of MOF-1 was 1.38 × 10 4 M −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the working process of the sensor is easy with a colorimetric response, and the sensor is portable. In this regard, compared to diverse fluorescence materials, the coordination polymers (CPs) or metal–organic frameworks (MOFs) show its meritocracy toward the detection of numerous analytes. MOFs have interesting structural features such as structural variety, host–guest complexation ability, , purposefully rooted reactive sites, , and ability to display structure–property relationship. These important features render to perform as an effective sensory material. Furthermore, the atomistically assigned functionalities assist in establishing of the sensing mechanism. Clearly the single crystallography , particularly, the single crystal to single crystal transformation is a brilliant technique to investigate the mechanism, but sometimes it is very challenging to get a single crystal structure of the sensor after analyte recognition. It has been observed that by tuning the MOF network with Lewis basic or uncoordinated functionality, the sensitivity of the probe can be significantly improved. , Importantly, for multisensory materials, it is expected that the sensor should have the ability to rationalize diverse signal transduction.…”
Section: Introductionmentioning
confidence: 99%